2016
DOI: 10.4314/jab.v95i1.4
|View full text |Cite
|
Sign up to set email alerts
|

A survey of plant-parasitic nematodes of yam farms in Awka-North local government area, Anambra state, Nigeria.

Abstract: Objective: Soil-inhabiting plant parasitic nematodes of yam were investigated in yam fields in Awka-North Local Government Area of Anambra state, Nigeria. Methodology and Results: Three farmlands each were randomly selected for sampling from the seven communities that make up the study area. Five yam plants were also randomly selected from each farm for sampling. Soil samples around the roots of each plant were collected using a hand trowel at a depth of 15-30 cm. The relative percentage composition of nematod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…are found in all temperate and tropical areas, and are among the most damaging plant pathogens worldwide [10] . [11] reported that Meloidogyne spp. was among the most prevalent plant parasitic nematode of yam farm in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…are found in all temperate and tropical areas, and are among the most damaging plant pathogens worldwide [10] . [11] reported that Meloidogyne spp. was among the most prevalent plant parasitic nematode of yam farm in Nigeria.…”
Section: Introductionmentioning
confidence: 99%